Roger Goodman: Japan’s ’International Youth’: The Emergence of a new Class of Schoolchildren - Andersen, Hanne (Tidsskriftet Antropologi, 1993)
Roger Goodman: Japan’s ’International Youth’: The Emergence of a new Class of Schoolchildren Anmeldes af Hanne Andersen